Sugar Control of the Plant Cell Cycle: Differential Regulation of Arabidopsis D-Type Cyclin Gene Expression - Riou-Khamlichi, Catherine (American Society for Microbiology, 2000)
In most plants, sucrose is the major transported carbon source. Carbon source availability in the form of sucrose is likely to be a major determinant of cell division, and mechanisms must exist for sensing sugar levels and mediating appropriate control of the cell cycle. We show that sugar availability plays a major role during the G(1) phase by controlling the expression of CycD cyclins in Arabidopsis. CycD2 mRNA levels increase within 30 min of the addition of sucrose; CycD3 is induced after 4 h. This corresponds to induction of CycD2 expression early in G(1) and CycD3 expression in late G(1) near the S-phase boundary. CycD2 and CycD3 induction is independent both of progression to a specific point in the cell cycle and of protein synthesis. Protein kinase activity of CycD2- and CycD3-containing cyclin-dependent kinases is consistent with the observed regulation of their mRNA levels. CycD2 and CycD3 therefore act as direct mediators of the presence of sugar in cell cycle commitment. CycD3, but not CycD2, expression responds to hormones, for which we show that the presence of sugars is required. Finally, protein phosphatases are shown to be involved in regulating CycD2 and CycD3 induction. We propose that control of CycD2 and CycD3 by sucrose forms part of cell cycle control in response to cellular carbohydrate status.